The Influence of Extracurricular Activities on Character Building of Students of SMPN 22 Makassar - Jamaluddin Jamaluddin; Syahrani Syam; Sirajuddin Saleh; Nasrullah Nasrullah (Jurnal Office, 2021)
The influence of extracurricular activities on character building of students at SMPN 22 Makassar. This study aims to determine the effect of extracurricular activities on the formation of student characters at SMPN 22 Makassar. This research is a quantitative study with a population of 505 students. The sample used in this study was 15 percent or 71 students. Data collection techniques used were questionnaire techniques (questionnaire), interviews, and documentation. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis. The results showed that the extracurricular activities of the students at SMPN 22 Makassar were in the quite good category with a percentage level of 56.88 percent which was seen from the indicators of krida and training/talent/achievement indicators and for the character of the students in the good category with a percentage level of 78.38 percent which was reviewed from indicators of a religious character, discipline, hard work, creative, independent, democratic and responsible. Based on the product-moment correlation analysis, it was stated that there was a relationship between extracurricular activities and the character-building of students in the medium category. The results of the simple regression analysis show that there is a positive and significant effect of extracurricular activities on the character building of students of SMP Negeri 22 Makassar